Counting Births, Deaths and Marriages: Knowledge and Perception of Heads of Households about Vital Statistics Registration in Southwestern Nigeria (Nigerian Journal of Health Sciences, 2025)
Background: Vital statistics provide crucial and critical information on the population in a country, which is useful for policy and planning, particularly in the health sector. This study aimed to assess the knowledge and perception about births, deaths and marriages registration among heads of households in Osogbo, Osun-State.Methodology: This was a descriptive cross sectional study conducted among 400 heads of households in Olorunda and Osogbo Local Government Areas of Osun State. Respondents were recruited using a multistage sampling technique. Data was analyzed using IBM SPSS and level of significance was set at p-value < 0.05.Results: The mean age of the respondents was 32.4 ± 10 years. A statistically significant association was found between knowledge of deaths registration and age (p=0.004), sex (p=0.016), ethnicity (p=0.037). Knowledge of marriage registration among respondents showed a statistically significant association with level of education as respondents with secondary and tertiary levels of education were 7 and 9 times more likely to have good knowledge of the marriage registration process respectively. A statistically significant association was found between perceptions about deaths registration, sex, educational status as well as the occupation of the respondents (p